(untitled) (Prithvi Academic Journal, 2026)
This study examined the influence of financial condition on dividend payout of twenty-one banks and financial institutions using quantitative secondary data from FY 2014/15 through 2023/24. Descriptive statistics and pooled ordinary least squares regression were used to analyze the data and derive the results. The study revealed that commercial banks paid the highest dividend, followed by development banks and finance companies. Capital adequacy and cash reserve ratios exceed the Nepal Rastra Bank standards, and the non-performing loan ratio showed high fluctuation. Besides, earnings per share positively influence dividend payout indicating higher earnings are associated with higher dividends. Capital adequacy, non-performing loan ratio, and leverage show a significantly negative influence on dividend payouts. Descriptive analysis shows that there is a significant mean difference in dividend payout across the three types of financial institutions, while there is insignificant negative impact of commercial bank dummy on dividends than that of other two sectors. Thus, the study concludes that dividend payout in the financial sector is largely driven by earnings capacity; however, high debt service obligations, poor asset quality, and excess capital adequacy lead financial institutions to adopt financial caution while struggling with profitability and efficiency. The study findings reinforce dividend relevance and signaling theories of dividend payout, as earnings per share is the key determinant. Practically, regulators like the central bank may review liquidity and capital adequacy to avoid excessive buffers, and bank managers need to emphasize improving earnings quality and controlling bad loans to enhance profitability.